LIVING HADIS: KONTRUKSI SOSIAL NILAI-NILAI TAHÄ€DÅª TAHÄ€BÅª DALAM TRADISI TONGEBAN - Moh. Jufriyadi Sholeh (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2023)
Cultural values and traditions in Muslim society cannot be separated from the values of the teachings of the Koran and the hadith of the Prophet. Every local culture and custom that exists during their lives will continue to be maintained with legality expressed or implied in the instructions of the Al-Qur'an and Hadith. The tongeban tradition among Madurese Muslims, which was built in the spirit of returning the visit of the male in-law's family by bringing a cake, is part of the living hadith in the form of implementing the values of the Prophet's hadith "tahadu tahabu", which recommends giving each other gifts to build mutual relationships. love. Life in marriage in Madura, especially in Sumenep, appears more harmonious when connected with the medium of tongeban. This tradition becomes a medium and forum for society to create a harmonious social life and conditions with an atmosphere of brotherhood. This tradition provides a strong encouragement to people to always help each other, respect each other, and care for each other. The tongeban tradition is a tradition and culture that has been passed down from generation to generation by the Madurese people, especially in Sumenep and has become a social fact. The continuity of this tradition continues from generation to generation, so it is a sign that the Madurese people, especially Sumenep, have realized the concept of social life exemplified by the Prophet and his companions in the form of harmony in life which includes all manifestations of good morals in various types of human relationships. Interdependence and cooperation in social piety and compassion, mutual give and take, at the individual, family and group levels.